The Ser/Thr protein kinase FonKin4-poly(ADP-ribose) polymerase FonPARP1 phosphorylation cascade is required for the pathogenicity of watermelon fusarium wilt fungus Fusarium oxysporum f. sp. niveum - Wang, Jiajing; Gao, Yizhou; Xiong, Xiaohui; Yan, Yuqing; Lou, Jiajun; Noman, Muhammad; Li, Dayong; Song, Fengming (Frontiers in Microbiology, 2024)
Poly(ADP-ribosyl)ation (PARylation), catalyzed by poly(ADP-ribose) polymerases (PARPs) and hydrolyzed by poly(ADP-ribose) glycohydrolase (PARG), is a kind of post-translational protein modification that is involved in various cellular processes in fungi, plants, and mammals. However, the function of PARPs in plant pathogenic fungi remains unknown. The present study investigated the roles and mechanisms of FonPARP1 in watermelon Fusarium wilt fungus Fusarium oxysporum f. sp. niveum (Fon). Fon has a single PARP FonPARP1 and one PARG FonPARG1. FonPARP1 is an active PARP and contributes to Fon pathogenicity through regulating its invasive growth within watermelon plants, while FonPARG1 is not required for Fon pathogenicity. A serine/threonine protein kinase, FonKin4, was identified as a FonPARP1-interacting partner by LC-MS/MS. FonKin4 is required for vegetative growth, conidiation, macroconidia morphology, abiotic stress response and pathogenicity of Fon. The S_TKc domain is sufficient for both enzyme activity and pathogenicity function of FonKin4 in Fon. FonKin4 phosphorylates FonPARP1 in vitro to enhance its poly(ADP-ribose) polymerase activity; however, FonPARP1 does not PARylate FonKin4. These results establish the FonKin4-FonPARP1 phosphorylation cascade that positively contributes to Fon pathogenicity. The present study highlights the importance of PARP-catalyzed protein PARylation in regulating the pathogenicity of Fon and other plant pathogenic fungi.